Discovery of the genus Leptophion Cameron, 1901, from Japan and the Palaearctic region, with description of two new species (Hymenoptera: Ichneumonidae: Ophioninae) - Shimizu, So; Watanabe, Kyohei (Zootaxa, 2015)
The genus Leptophion Cameron, 1901, which belongs to the subfamily Ophioninae Shuckard, 1840, is recorded from Japan and the Palaearctic region for the first time based on two new species, L. parvus sp. nov. from Amamioshima Island and L. septentrionis sp. nov. from Yakushima and Amamioshima Island. A key to the Japanese and Taiwanese species is also provided.